Asthma exacerbation – diagnosis and treatment: the dos, don’ts and maybes - Pawliczak, Rafał (Alergologia Polska - Polish Journal of Allergology, 2025)
The treatment of asthma exacerbations remains a challenging aspect of asthma therapy, often eluding standard management protocols. General practitioners – and even pulmonologists or allergists – often treat asthma exacerbations in a hurry, making decisions without appropriate diagnostic tools. Consequently, management is often suboptimal, delaying asthma control and increasing the risk of future exacerbations. Worse still, the lack of standardised procedures often leads to conflicts between differing clinical guidelines. In some cases, this results in entirely inappropriate therapeutic strategies. This article aims to support the standardisation and clarification of treatment approaches for asthma exacerbations in adult patients.